2014
DOI: 10.1364/ol.39.003094
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic control of wideband slow wave in graphene based waveguides

Abstract: Enlarged group index has been reported previously when surface plasmons propagate through the graphene sheet, yet a clear slow wave performance in graphene has not been explored. We proposed and numerically analyzed here for the first time to the best of our knowledge an extremely wideband slow surface wave in a graphene-based grating waveguide. The strongly delayed wave (120Δf>0.7 THz) can be dynamically controlled via the gate-voltage dependent optical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…In general, the ability of plasmonic structures based on graphene to slow down the propagation of light rivals their metal-based counterparts 18 22 51 . The slowdown factor is even 3 times larger than that of the reported graphene structure 33 . In agreement with the results presented in [19], we find that the slowdown factor strongly depends on the substrate groove depth at a given operating wavelength.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…In general, the ability of plasmonic structures based on graphene to slow down the propagation of light rivals their metal-based counterparts 18 22 51 . The slowdown factor is even 3 times larger than that of the reported graphene structure 33 . In agreement with the results presented in [19], we find that the slowdown factor strongly depends on the substrate groove depth at a given operating wavelength.…”
Section: Resultsmentioning
confidence: 65%
“…In recent years, graphene has been introduced to the field of plasmonics 26 and offers new ways to manipulate and confine light on the nanoscale. The intriguing properties of SPPs in graphene based structures were investigated in recent years 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 . For example, Vakil et al found that graphene with spatially modulated conductivity patterns can be used as a one-atom-thick platform for transformation optics 27 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene is an anisotropic material [16][17], in which only the in-pane permittivity components //  can be tuned by the external voltages while the permittivity component   perpendicular to the graphene plane always stays as a constant 2.5 [17]. And the in-plane permittivity component of graphene can be described as [18]:…”
Section: Mode Indexmentioning
confidence: 99%
“…2(a). In the vicinity of the transparency window, the group index is large and of great dispersion, suggesting the light is very slow and highly dispersive, which is very different from the slow light effect in the periodic graphene-based waveguides that is with low group velocity dispersion [20]. To further investigate the properties of this EIT-like phenomenon, the amplitude distributions of the magnetic field corresponding to the two transmission dips and the transmission peak are illustrated in Fig.…”
mentioning
confidence: 99%